FRI0104 Long-Term Followup of Biologic Agents in Patients with Rheumatoid Arthritis. (15th July 2016) - Kaneko, Y.; Kondo, H.; Ohta, M.; Takeuchi, T.
Abstract : Background: Biologic agents have altered treatment strategy and improved outcome in rheumatoid arthritis (RA). More than 10 years have passed since the emergence of the first biologic agent, and the switch to alternative agent for insufficient efficacy and intolerance is not infrequent. However, the continuation rate of biologic agents and reasons for discontinuation in a long-term are unclear. Objectives: To evaluate followup data for more than10 years of biologic agents in patients with RA. Methods: Patient who started biologic agents including infliximab, etanercept, adalimumab, tocilizumab and abatacept for RA between 2003 and 2013 were enrolled in the study. The continuation rate was calculated by Kaplan-Myere analysis, and reasons for discontinuation were retrospectively investigated. Factors contributory to the continuation rate were identified. The analyses were performed in all patients, and subsequently in patients on individual biological agents. Results: A total of 1500 biologic agents were introduced in 1036 patients with RA for the 11 years. At the initiation of biologic agents, the mean age was 57.2 years old, the rate of female 82.5%, disease duration 103 months, rheumatoid factor positivity 78.8% DAS28 4.90, and health assessment questionnaire 1.09. Methotrexate (MTX) was used in combination with biologic agents in 81.1%. Overall continuation rate was 68.7% at year 3, 58.8% at year 5, and 27.6% at year 10. Reasons for discontinuation were insufficient efficacy in 64.3% and adverse effect in 45.7%. Baseline characteristics to predict the continuation of biologic agents were the concomitant use of MTX (OR=1.61, P=0.03), lower baseline values for 28 joints (DAS28, OR=1.14, P=0.02) and shorter disease duration (OR=1.01, P=0.03). In bio-naïve patients, continuation rate was 69.3% at year 3, 59.4% at year 5, and 28.5% at year 10). In terms of individual biologic agents, high continuation rate was ascribed to lower disease activity for infliximab (OR=1.32, P=0.001), the concomitant use of MTX for etanercept (OR=1.22, P=0.03) and adalimumab (OR=1.53, P=0.04), shorter disease duration for abatacept (OR=1.00, P=0.05). No specific factor for tocilizumab continuation was found. Conclusions: In the initiation of biologic agents, patients using concomitant MTX with shorter disease duration in lower disease activity were inclined to continue the biologic agents. Factors for good continuation rate were different among biologic agents. The present study can contribute optimal usage of biologic agents in the treatment of RA. Disclosure of Interest: Y. Kaneko Speakers bureau: Abbvie, Eisai Pharmaceutical, Chugai Pharmaceutical, Bristol Myers Squibb, Astellas Pharmaceutical, Mitsubishi Tanabe Pharma Corporation, Pfizer, Janssen, Santen, Kyowa Hakko Kirin and UCB, H. Kondo: None declared, M. Ohta: None declared, T. Takeuchi Grant/research support from: Astellas Pharma, Bristol–Myers K.K., Chugai Pharmaceutical Co, Ltd., Daiichi Sankyo Co., Ltd., Eisai Co., Ltd., Janssen Pharmaceutical K.K., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Sanofi–Aventis K.K., Santen Pharmaceutical Co., Ltd., Teijin Pharma Ltd., abbvie GK, Asahikasei Pharma Corp., Taisho Toyama Pharmaceutical Co., Ltd. Janssen Pharmaceutical K.K., Astra Zeneca K.K., Eli Lilly Japan K.K., Novartis Pharma K.K., Abbvie GK., Speakers bureau: Astellas Pharma, Bristol–Myers K.K., Chugai Pharmaceutical Co, Ltd., Daiichi Sankyo Co., Ltd., Eisai Co., Ltd., Janssen Pharmaceutical K.K., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Abbvie GK, Asahikasei Pharma Corp., Taisho Toyama Pharmaceutical Co., Ltd. Janssen Pharmaceutical K.K., Astra Zeneca K.K., Eli Lilly Japan K.K., Novartis Pharma K.K.